2021
DOI: 10.1108/wjemsd-02-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of entrepreneurship education on innovative start-up intention: the mediating role of entrepreneurial mind-sets

Abstract: PurposeEntrepreneurship education at universities aims to create entrepreneurial thinking and spread the culture of entrepreneurial awareness, skills and attitudes to students to stimulate their entrepreneurship intentions as graduates. This study investigates the impact of entrepreneurship education on innovative start-up intention as well as the mediating role of entrepreneurial mind-sets of university students.Design/methodology/approachStructural equation modeling (SEM) was used for analysis with (n = 204)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…A combination of a company's resources and capabilities will likely give a small business a good start (Bauman & Lucy, 2021). This result is different from previous research (Morris et al 2017), which showed a negative relationship between university resource support and the scope of startup activities, but these findings support research from (Hanandeh et al 2021;Hassan, 2020;Saeed et al 2015).…”
Section: Individuals Carry Entrepreneurial Competenciescontrasting
confidence: 64%
See 1 more Smart Citation
“…A combination of a company's resources and capabilities will likely give a small business a good start (Bauman & Lucy, 2021). This result is different from previous research (Morris et al 2017), which showed a negative relationship between university resource support and the scope of startup activities, but these findings support research from (Hanandeh et al 2021;Hassan, 2020;Saeed et al 2015).…”
Section: Individuals Carry Entrepreneurial Competenciescontrasting
confidence: 64%
“…Growth in market share problems, and share networks and resources (Hanandeh et al 2021;Mihalache et al 2014;Salihu, 2016).…”
Section: Business Performancementioning
confidence: 99%
“…There are indications of those investigations among international students when considering the role of exposure to entrepreneurial education as a factor that instigates entrepreneurial innovativeness among these students. Findings on the contributions or influence of entrepreneurial education on entrepreneurial innovativeness, opportunity recognition and entrepreneurial intention seem saturated [20][21][22][23][24]. Nevertheless, there is no unanimity among the numerous available investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, exploring the reasons why individuals have intents and behave ADHD symptoms as a moderator entrepreneurially as well as investigating which antecedents contribute to or impede forming entrepreneurial intentions and actions are increasingly interested in current scholar studies (e.g. Hanandeh et al, 2021;Qazi et al, 2021). Recently, a psychological health crisis is identified to be occurring across the global scope (Rajah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, exploring the reasons why individuals have intents and behave entrepreneurially as well as investigating which antecedents contribute to or impede forming entrepreneurial intentions and actions are increasingly interested in current scholar studies (e.g. Hanandeh et al. , 2021; Qazi et al.…”
Section: Introductionmentioning
confidence: 99%